2008
DOI: 10.1016/j.molcel.2008.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Bypassing Sir2 and O-Acetyl-ADP-Ribose in Transcriptional Silencing

Abstract: The yeast Sir2/3/4 protein complex forms a repressive heterochromatin-like structure that confers transcriptional silencing. The complex nucleates at silencers and then spreads distally by a process that requires the NAD+-dependent deacetylase activity of Sir2 and the affinity of Sir3/4 for deacetylated histone tails. A byproduct of the Sir2 reaction, O-acetyl-ADP-ribose (OAADPr), is thought to aid spreading by binding one of the Sir proteins. We have used a protein chimera approach to reexamine the essential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 42 publications
1
35
0
Order By: Relevance
“…Interestingly, a recent study reported apparently OAADPRindependent silencing by a fusion protein between the NAD + -independent HDAC Hos3 and Sir3 (40). One explanation to reconcile this observation with our data is that OAADPR is required for the interaction and recruitment of Sir2/Sir4 to Sir3.…”
Section: Discussionsupporting
confidence: 85%
“…Interestingly, a recent study reported apparently OAADPRindependent silencing by a fusion protein between the NAD + -independent HDAC Hos3 and Sir3 (40). One explanation to reconcile this observation with our data is that OAADPR is required for the interaction and recruitment of Sir2/Sir4 to Sir3.…”
Section: Discussionsupporting
confidence: 85%
“…A binding site for the metabolite has yet to be defined within the Sir2/3/4 complex. To test whether OAADPr was essential for silencing and whether other deacetylases could substitute for Sir2, silent chromatin was assembled in vivo with Hos3, an Rpd3-family deacetylase that neither consumes NAD nor produces OAADPr (Chou et al 2008). Hos3 was targeted to assembling silent chromatin domains by creating a Sir3-Hos3 fusion protein.…”
Section: Lessons Learned From Silent Chromatin Reconstitutionmentioning
confidence: 99%
“…The effect was dramatic with the Sir2,3,4p complex, but is also quite significant with Sir3p alone, suggesting that it is the key target (Martino et al 2009). The evidence against this hypothesis is based on a Sir3p-Hos3 fusion protein used to demonstrate that telomeric silencing can occur in the absence of O-AADPR (Chou et al 2008). Hos3 is an NAD + -independent deacetylase that does not produce O-AADPR, nor does it normally deacetylate histones.…”
Section: O-aadprmentioning
confidence: 99%
“…Hos3 is an NAD + -independent deacetylase that does not produce O-AADPR, nor does it normally deacetylate histones. When fused in-frame to the C terminus of Sir3p, it deacetylates histones at silent loci as measured by ChIP, and this effectively silences DNA (Chou et al 2008). However, while it does not silence as well as wildtype yeast, it does silence as well as a Sir3-Sir2p fusion protein (Chou et al 2008).…”
Section: O-aadprmentioning
confidence: 99%